2014
DOI: 10.1590/s0100-72032014000100005
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and serum cortisol levels, salivary alpha-amylase and unstimulated whole saliva flow rate in pregnant and non-pregnant

Abstract: The prevalence of diseases with the risk of vertical transmission is important in women with spontaneous abortion, indicating the need for more research in order to investigate the etiology of abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
(72 reference statements)
0
8
2
2
Order By: Relevance
“…Our finding showed an increase in SFR in the second trimester of pregnancy while the study conducted by Naveen S et al, in 2013 found a significant increase in the SFR in the second trimester pregnant women compared to non-pregnant women [10]. Our findings are contrary to the study conducted by Abrao ALP, et al, in 2014 who concluded that the median unstimulated SFR showed no differences among trimesters of pregnancy [13]. Pregnancy induces decreased gastroesophageal sphincter tone and prolonged gastric emptying times.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding showed an increase in SFR in the second trimester of pregnancy while the study conducted by Naveen S et al, in 2013 found a significant increase in the SFR in the second trimester pregnant women compared to non-pregnant women [10]. Our findings are contrary to the study conducted by Abrao ALP, et al, in 2014 who concluded that the median unstimulated SFR showed no differences among trimesters of pregnancy [13]. Pregnancy induces decreased gastroesophageal sphincter tone and prolonged gastric emptying times.…”
Section: Discussioncontrasting
confidence: 99%
“…As noted in the introduction, results of these studies are not consistent and may be even contradictory. 6,12,13,15,[19][20][21][22][23][24] Among all the analysis performed, and taking together previous studies and the present study, we can confidently assume that pregnancy reduces non-stimulated saliva pH. 6,12,13,19,21 The decrease of saliva pH during pregnancy may be partially justified by the higher number of daily meals.…”
Section: ■ Discussionmentioning
confidence: 58%
“…Previous studies showed higher α-amylase levels in saliva during pregnancy, 15,24 in parallel with higher blood levels.…”
mentioning
confidence: 83%
“…various cognitive conditions and in the presence of mental stress and anxiety (31). Previously, when an individual is exposed to the stressful situation, the neuroendocrine systems are activated and secrete substances such as adrenaline and cortisol, promoting physiological reactions in response to stress (32).…”
Section: Discussionmentioning
confidence: 99%